Revelation, four views : a parallel commentary - Gregg, Steve, 1953- (Nashville, Tenn. : T. Nelson Publishers, 1997)
An even-handed summary of the four traditional views of Revelation in parallel columns. This convenient presentation not only gives you the information you need on these key views, but also informs you about outstanding commentators on the book of Revelation throughout much of church history
The seven letters : Revelation 1-3 -- The seven-sealed scroll : Revelation 4-7 -- The seven trumpets : Revelation 8-10 -- The 1260 days : Revelation 11-13 -- The seven last plagues : Revelation 14-16 -- The great Babylon : Revelation 17-19 -- The millennium : Revelation 20 -- The new creation : Revelation 21-22
Includes bibliographical references and indexes
Keywords: Bible. -- Commentaries